The teaching of literature in using cognitive poetics: its practicality, strengths and challenges - Abdullah, Suhaila; Idrus, Faizah; Sheikh Ahmad, Ismail (Universiti Kebangsaan Malaysia, 2024)
This paper explores the use of a theory known as cognitive poetics as an approach to teach literature to students in private secondary schools, Malaysia. Cognitive poetics stands as an inter-disciplinary field that revolves around the science of reading literature by using psychology and cognition (Stockwell, 2020). It supports a natural process of reading that creates an interaction between the reader and the literary text. In this qualitative study, the authors opt to use three key concepts of cognitive poetics, namely figures and grounds, prototypes and reading as well as discourse worlds and mental spaces. The rationale of this study is to explore the strengths and challenges in using the key concepts contained in cognitive poetics and whether this theory is practical to be applied in the teaching of literature. This study sought to find answers whether educators could or could not adopt cognitive poetics in teaching literature and whether this approach could garner students’ interest in reading and studying literature. Two phases of semi-structured interviews and class observations were conducted, involving three teachers who taught English Literature in three private schools. The findings show that cognitive poetics could assist the students to fathom the psychology of the authors and characters in literary works. This research hopes to introduce a relatively new theoretical approach to the teaching of literature in secondary schools in Malaysia.